The determinants of house price in Malaysia / Raja Nurul Huda Raja Zakariah and Siti Fatimah Md Termizi - Raja Zakariah, Raja Nurul Huda; Md Termizi, Siti Fatimah (Faculty of Business and Management, 2019)
This paper aim at finding out the determinants of house prices in Malaysia which the house price is monitor based on the house price index (HPI). The variables are considered are gross domestic product (GDP), inflation (INF) and lending rate (LR). This study required 9 years data which is equal to 33 data by quarterly for each variable from 2010 until 2018. Methodology used for this study is using Multiple Linear Regression with series data. Thereafter, econometric test is to be conducted to observe the relationship of the independent variables with house price which is house price index (HPI). Interactive software package E-view would be used for testing and analyzing the data collected. This study is attempting to investigate there is a significant relationship between the independent variables with the house price index (HPI) and which variables contributes most to house price. Findings from previous study mostly show that gross domestic product (GDP), inflation (INF) and lending rate (LR) has a significant role in the determination of house price. As guidance to the past research that have been done, this study will examine the relationship between impact of independent variables and house price.